PROMOSI STUDIO TENUN PINAN KABU MELALUI VIDEO DOKUMENTER - LUTFI IZUDDIN IZUDDIN; syafwandi syafwandi (DEKAVE : Jurnal Desain Komunikasi Visual, 2021)
The aim of the designing documentary video is to promote Studio Tenun Pinan Kabu in providing information visually about revitalization of Minangkabau's old songket along with the procedure of manufacturing which become the main focus of this project.The design method used is the 4-D method: Define (Definition), Design (design), Develop (Development), Disseminate (deployment); (Nasrul Kamal: 2016).The analysis method uses 5W+1H to obtain required data according to design needs. The documentary video of Studio Tenun Pinan Kabu produce through creative program: pre-production, production, and post-production phase.The result of Tenun Pinan Kabu documentary video as the main media can increase economic value of Studio Tenun Pinan Kabu, raising the numbers of enthusiasts, and it can be educational video about revitalization of Minangkabau's old songket. The supporting tools of the main media are in form of posters and X banners which indirectly become the extended information of Tenun Pinan Kabu Studio through the audience which use one of the supporting media in form of masks, tote bags, stickers, clothes, and MUG.Keywords: documentary video, revitalization, economic value